Temperature and RH response of polymer CYTOP FBG treated by gamma radiation - Chapalo, Ivan; Gusarov, Andreï I.; Chah, Karima; Ioannou, Andreas; Posporis, Andreas; Nan, Ying-Gang; Kalli, Kyriacos; Megret, Patrice (My University, 2023)
Polymer fiber Bragg grating (FBGs) demonstrate a wider strain range and stronger temperature sensitivity compared to standard silica FBGs. Besides, their advantageous feature is sensitivity to humidity that enables FBG-based relative humidity (RH) sensing. However, practical realization of RH sensors requires temperature cross-sensitivity elimination. A certain optimal fiber pre-strain and gamma irradiation of perfluorinated (CYTOP) FBGs up to certain optimal dose are potential recently proposed solutions for this problem. In this work, we investigate temperature and RH response of FBGs inscribed line-by-line in a few-mode polymer fiber with 20-µm CYTOP core and 250-µm XYLEX overclad. We compare the cases of the pristine FBG sample and the sample received 200 kGy irradiation dose. The 200-kGy dose was previously confirmed to provide temperature sensitivity minimization at 40%RH. Here, we show the close-to-zero temperature sensitivity (≈1pm/℃) for 200-kGy dose at high RH value of 89%. Besides, we briefly analyze the stabilization process of FBGs response to strong and quick RH changes.
Keywords: CYTOP; fiber Bragg gratings; fiber optic sensors; perfluorinated polymer; Polymer optical fiber